Controlling Nutritional Status Score As a Predictive Marker for Patients With Implantable Left Ventricular Assist Device. Issue 2 (February 2020) - Saito, Akihito; Amiya, Eisuke; Hatano, Masaru; Shiraishi, Yasuyuki; Nitta, Daisuke; Minatsuki, Shun; Maki, Hisataka; Hosoya, Yumiko; Tsuji, Masaki; Bujo, Chie; Nawata, Kan; Kinoshita, Osamu; et al.
Abstract : Although a correlation between the nutritional status and the prognosis of patients with heart failure has been suggested, a correlation between the nutritional status and outcomes after the left ventricular assist device (LVAD) implantation remains unclear. We aimed to investigate the efficacy of the Controlling Nutritional Status (CONUT) score (range 0–12, including serum albumin, total cholesterol, and lymphocytes) as a nutritional index in speculating the prognosis of patients undergoing LVAD implantation. We examined 63 consecutive patients who underwent the continuous-flow LVAD implantation. Using the preoperative CONUT score, patients were categorized into two groups: lower CONUT score (0–4: normal to mild malnutrition) and higher CONUT score (5–12: moderate to severe malnutrition). We compared for the backgrounds and the clinical events after LVAD implantation. The higher CONUT group exhibited a significantly higher mean right atrial pressure (10.9 ± 4.7 vs. 7.3 ± 4.1 mmHg; p = 0.0019). In that group, the mortality rate was significantly higher (25% vs. 2.6%; p = 0.0059) and the Kaplan–Meier analysis showed lower survival rate. Furthermore, more bleeding events significantly occurred in the higher CONUT group. The preoperative CONUT score may reflect systemic venous congestion and offer a useful prognostic index of clinical courses after LVAD implantation.